المهارات الترجمانية الماورائية المعرفية لدى الترجمان: Metacognitive interpreting skills - boulahia , Sara; kellou, yasmine (Maalim, 2023)
Researchers in interpreting studies are no longer denying that interpreting process must be cognitive, and take into consideration that translation should be tackled as both process and product. Cognitive approach within interpreting studies is more than a psychological sight into the interpreter’s performance; it is a high quality and success indicator of the interpreter achievement whether at the academic level or the professional one. From other disciplines such as: psychology, cognitive sciences and artificial intelligence, researchers all together tried to unveil the cognitive side of human in order to help in building up cognitive aptitudes models. It is a way to enhance interpreter’s performance by identifying the “must-have” cognitive aptitudes and having a cognitive platform for future empirical studies.